Suitability and Allocation of Protein-Containing Foods According to Protein Tolerance in PKU - Gama, Maria Inês (2022)
Funding Information: No funding was required for this project. All work was conducted as part of routine service by all dietitians involved. Publisher Copyright: © 2022 by the authors.